RETRACTED: Decoupling of greenhouse gas emissions from livestock industrial development: Evidence from China Agricultural Green Development Modern Zone - Liu, Zixuan; Ahmad, Mahmood; Li, Guojing; Yang, Yadong; Liu, Yang; Gao, Mingjie; Luo, Qiyou (Frontiers in Environmental Science, 2022)
China Agricultural Green Development Modern Zone (CAGDMZ) constitute a demonstration area for achieving green and sustainable development of Chinese agriculture. It plays a role in demonstrating high-quality agricultural development and environmental protection. As a result, a coordinated interaction among livestock greenhouse gas (GHG) emissions and rapid industrial livestock evolution in the CAGDMZ is of great concern to China’s government. In this paper, we were the first to research the decoupling relationship between livestock GHG emissions and industrial development by using data from 165 CAGDMZ of China from 2010-2019 at different regional scales and long time series. On this basis, we further explored the factors affecting livestock GHG emissions by using the Logarithmic Mean Divisia Index method (LMDI). Our analysis revealed that the amount of GHG emissions from livestock in the CAGDMZ showed a rising and then declining trend. Pigs, nondairy cattle and sheep were the main targets of livestock GHG emission reductions. There were obvious spatial differences in livestock GHG emissions. 17 provinces’CAGDMZ achieved emissions reductions, but 14 provinces’ CAGDMZ increased livestock GHG emissions. The Northeast CAGDMZ had the highest livestock GHG emissions and the Eastern CAGDMZ had the largest livestock GHG deceleration. Furthermore,the decoupling status in the CAGDMZ were unstable. Most provinces or regions of the CAGDMZ maintained the economic growth of livestock while curbing the excessive growth of GHG emissions. Only a few of them achieved a win-win situation of livestock output value increase while GHG emission reduction. Moreover, the comprehensive effect showed an inverted "U" trend. Production efficiency was the most major contributor to livestock GHG emissions reductions. Economic development factor and labor scale factor were the main driving factors for increasing GHG emissions. Industrial structure factor shifted from promotion to suppression of livestock GHG emissions. Therefore, some policies to accomplish the CAMGDDZ’s long-term development were proposed.